Relationship between workplace conflict, job certainty, job opportunities, and job stress - Siwidati, Anggit Wirama; Dwiyanti, Endang; Astutik, Ratna Hafitri; Ardhianingrum, Galuh Saraesti; Astrini, Nahdia Retno; Deismawaranti, Asri; Damayanti, Dwi; Hapsari, Maria Saraswati Kinasih (Universitas Gadjah Mada, 2025)
Purpose: This study analyzes the influence of individual capacity and task demands on Job stress levels.Methods: This study uses an observational, cross-sectional design. All 33 workers who became the population were included as research samples. Data were collected through questionnaires and observations and analyzed using the gamma coefficient to measure the strength and direction of relationships among individual capacity, task demands, and job stress.Results: Most workers reported mild to moderate stress levels. Workplace conflict demonstrated a strong, positive relationship with job stress (γ = 0.622), indicating that higher workplace conflict is associated with greater job stress. Job certainty showed a moderate, negative relationship with job stress (γ = -0.543), indicating that lower job certainty is associated with higher job stress. Job opportunities had a powerful and negative relationship with job stress (γ = -0.907), indicating that limited employment opportunities significantly increase stress levels.Conclusion: Mental workload and job opportunities have the most substantial relationship with job stress, followed by education, tenure, physical workload, and work conflict. Therefore, interventions to address this issue by strengthening job security policies are needed to minimize stress and improve overall employee well-being.